Endothelin-1 level as a predictor of hepatopulmonary syndrome in liver cirrhosis - Dr Darmadi; Riska Habriel Ruslie (Medicinski glasnik, 2020)
Aim: To determine the role of endothelin (ET)-1 in predicting hepatopulmonary syndrome (HPS) in patients with liver cirrhosis. Methods: A cross sectional study involving 80 liver cirrhosis patients aged 18 years or older was conducted in Adam Malik General Hospital Medan, Indonesia between July 2017 and June 2018. HPS diagnosis was confirmed from the presence of liver cirrhosis, abnormal oxygenation, and intrapulmonary vascular dilatations (IPVD). ET-1 level was measured from serum sample using ELI-SA method. Patients with coexisting primary pulmonary pathology and intrinsic heart disease were active smokers, and those who declined to participate were excluded. Statistical analysis was conducted at 95% confidence interval. p<0.05 was considered significant. Results: Majority the patients were male (56.3%) and had higher educational background (62.5%). Mean age of the patients was 51.3 (SD=12.6) years. The prevalence of HPS was 21.2%. The patients with HPS had higher ET-1 level compared to those without HPS (p<0.001). The patients with hepatic encephalopathy had 2.917 times higher risk for suffering from HPS, while the patients with Child Pugh score A had lower risk (0.738 times) for having HPS compared to subjects with Child Pugh score B and C. ET-1 level >187.5 mg/L had sensitivity and specificity for predicting HPS in subjects with liver cirrhosis of 82.35% and 81.25%, respectively. Conclusion: ET-1 could be used as a promising marker for HPS in patients with liver cirrhosis. ET-1 level of >187.5 mg/l had a good accuracy in predicting HPS in liver cirrhosis patient.
Keywords: endothelin; hepatopulmonary syndrome; liver cirrhosis